Olympic Education for All? An opportunity to take the Pan-Iberic Association of Olympic Academies to new heights, together. - Villegas-Estrada, Carlos Eduardo (Πανεπιστήμιο Πελοποννήσου, 2024)
The study presents an Olympic Education "unofficial ranking" of the National Olympic Academies (NOAs) affiliated to the Pan-Iberic Association of Olympic Academies (APAO), which marks the level of commitment to satisfy their missions. The empirical benchmarking study is founded on two main dimensions: Engagement and Governance and is motivated by the recommendations of Olympic Agendas 2020 and 2020+5. The study is organized as follows: Starts with the genesis of APAO since its creation by Conrado Durántez in 1988. Then an analysis of the implementation of Olympic Education programs in 29 APAO´s NOAs considering 10 indicators, used to create the three-level ranking of the Academies. The results of the research shows, with few exceptions, that the NOAs present low level of activity and are not fulfilling the mandate of promoting Olympic Education as established by the International Olympic Academy (IOA); not corresponding to the opportunities given by APAO and the IOA. The search for possible causes of such a poor performance, motivated additional research to analyze the participation of lecturers from Pan-Iberic countries in the sessions held in Olympia; as a result, from 649 lecturers invited to 70 sessions between 2000 and 2021, only 47 (7.2%) came from Pan-Iberic countries, and only 16 scholars came from Spanish speaking countries; bringing up the thesis of the Eurocentric character of the Olympic Movement. Consequently, the author leaves the door open with suggestions for future research and recommendations for practice, underscoring the opportunities available for the Pan-Iberic Olympic Academies as protagonists of today´s society.
The present academic work pays a live tribute to a true leader by example and action that has inspired most of us. Conrado Durántez Corral is, without a doubt, the most important Spanish speaking protagonist of the Olympic Movement for the last 7 decades. Conrado Durántez not only was instrumental in the creation of the Pan-Iberic Association of Olympic Academies (APAO), but also in that of the very own International Olympic Academy and in scores of National Olympic Academies, starting with the very Spanish back in 1960´s. Personally, I owe Conrado my designation as a member of the Colombian Olympic Academy, and all that has followed, after having the immense privilege of, accidentally, sharing with him the central stage on the commemoration of the sesquicentenary of the birth of our mentor, baron Pierre de Coubertin; solemn event held in the premises of the Colombian Olympic Committee in Bogotá, in June of 2013. After my intervention, he sentenced: "People like this are who should make part of the National Olympic Academies”; and here we are! Special thanks as well to the supervising professors of this thesis, Cesar Torres, Emilio Fernández-Peña, and the dean Costas Georgiadis to whom I´m incredibly grateful for their patient! To my wife Liliana, and our friend, professor Neu from Austria, for their permanent encouragement to finish the job.
Keywords: Ολυμπιακό κίνημα; Ολυμπισμός; Ολυμπιακή παιδεία; Διεθνής Ολυμπιακή Ακαδημία; Olympic movement; Olympism; Olympic education; International Olympic Academy; APAO; NOAs; Olympic education; Engagement; Governance; Opportunities